Optimalisasi strategi perbankan syariah untuk mendorong inklusi keuangan syariah yang berkelanjutan - Luay, Luqiana Khuld (Maliki Interdisciplinary Journal, 2025)
This research discusses the efforts made by Islamic banking to optimize existing strategies in support of sustainable Islamic financial inclusion. The initiatives undertaken by Islamic banks include providing financial education through digital innovations that facilitate public access to financial services, fostering strong collaborations between Islamic banks, the government, and other financial institutions, and prioritizing Islamic values in operations as well as in the development of relevant products and services that align with these values. This study employs a literature review methodology, utilizing qualitative data obtained from articles relevant to the discussed issues. Islamic banking also cooperates with other financial institutions including the government as a form of effort to maintain the relevance of products and services in accordance with regulations and community needs. Finally, Islamic banking strives to always prioritize and implement Islamic values ​​in offering financial products and services and in carrying out its operations.